Effects of renal denervation on the course of cardiorenal syndrome: insight from studies with fawn-hooded hypertensive rats - Doul, J; Gawrys, O; Škaroupková, P; Vaňourková, Z; Szeiffová Bačová, B; Sýkora, M; Maxová, H; Hošková, L; Šnorek, M; Sadowski, J; Táborský, M; Červenka, L (Physiological research, 2024)
Combination of chronic kidney disease (CKD) and heart failure (HF) results in extremely high morbidity and mortality. The current guideline-directed medical therapy is rarely effective and new therapeutic approaches are urgently needed. The study was designed to examine if renal denervation (RDN) will exhibit long-standing beneficial effects on the HF- and CKD-related morbidity and mortality. Fawn-hooded hypertensive rats (FHH) served as a genetic model of CKD and fawn-hooded low-pressure rats (FHL) without CKD served as controls. HF was induced by creation of aorto-caval fistula (ACF). RDN was performed 28 days after creation of ACF and the follow-up period was 70 days. ACF FHH subjected to sham-RDN had survival rate of 34 % i.e. significantly lower than 79 % observed in sham-denervated ACF FHL. RDN did not improve the condition and the final survival rate, both in ACF FHL and in ACF FHH. In FHH basal albuminuria was markedly higher than in FHL, and further increased throughout the study. RDN did not lower albuminuria and did not reduce renal glomerular damage in FHH. In these rats creation of ACF resulted in marked bilateral cardiac hypertrophy and alterations of cardiac connexin-43, however, RDN did not modify any of the cardiac parameters. Our present results further support the notion that kidney damage aggravates the HF-related morbidity and mortality. Moreover, it is clear that in the ACF FHH model of combined CKD and HF, RDN does not exhibit any important renoprotective or cardioprotective effects and does not reduce mortality. Key words Chronic kidney disease, Heart failure, Renal denervation, Fawn-hooded hypertensive rats.
Keywords: Animals; Kidney; hypertenze; Heart Failure; Cardio-Renal Syndrome; srdeční selhání; Sympathectomy; denervace; Hypertension; sympatektomie; Male; Denervation; kardiorenální syndrom; modely nemocí na zvířatech; Disease Models, Animal; krysa rodu Rattus; mužské pohlaví; zvířata; ledviny; Rats